Managing Education Funds: Effective Tips in Financing Management - Cecep Anwar; Fadhila Mizana (Zona Education Indonesia, 2023)
Education financing management plays an important role in achieving education goals and upgrading the quality of education. One way to upgrade the quality of education is to pay attention to the national standards of education applicable in Indonesia, including financing standards. Available school finances need to be managed using management functions so that financing management can be carried out effectively and efficiently. Functions in financing management include planning, bookkeeping, use of finance or spending, recording, supervision, and accountability. Education financing management is one of the keys to the success of teaching and learning activities in schools because the cost of education has a linear correlation with the quality of education